The story of "Bishr and Hind" and its reflection in Persian poetry - Mahmud Moddaberi (ادبیات تطبیقی, 2019)
Bishr and Hind is the name of an old story of Arab lovers, which was set in Medina at the time of Prophet of Islam. Ibn al-Nadim has narrated the names of both of them along with the names of other famous Arab lovers. The story is about Hind, a married woman, falling in love with Beshr, a religious person or a poet who always went to the Prophet’s Mosque. But in the end, they could not be together, and they both died and were buried next to each other. This story has close narratives in Arab literature, and for the first time, Ibn al-Sarraj al-Qari, a famous spokesman and litterateur of the 5th century A.H., has narrated it in the Masare' el-'Oshshaq in verse and prose. In Persian literature, given few references made by poets, such as Fakhr ad-Din Iraqi, Awhadi Maraghai and Khwajou Kermani, it is revealed that this story was known at least until the Ilkhani period. Hamd-Allah Mostowfi has attributed the Masnavi Bishr and Hind to Najib ad-Din Jorbazaqani and Amin Ahmad Razi in his tadhkirah Haft Iqlim, has narrated eleven verses of it in the name of this poet of the 7th century A.H. Currently, there is no manuscript of this book in hand.